Emotional Intelligence Among School Teachers in Oman - Al-Busaidi, Saleh; Aldhafri, Said; Alrajhi, Marwa Nasser; Alkharusi, Hussain; Alkharusi, Badar; Ambusaidi, Abdullah; Alhosni, Khoula (Alberta Journal of Educational Research, 2019)
This paper sheds light into the role of emotional intelligence in school teaching. It reports the findings of a study that sought to investigate the emotional intelligence of 4,098 school teachers in the Sultanate of Oman in five dimensions using the Schutte Emotional Intelligence Scale (SEIS). The study also measured the relationship between teachers’ emotional intelligence and a number of demographic teacher and school variables. The results showed that teachers’ emotional intelligence was high in all five dimensions. There were variations in teachers’ emotional intelligence based on certain teacher and school variables. Key words: job satisfaction, Sultanate of Oman, teachers’ emotional intelligence. Cet article fait la lumière sur le rôle de l’intelligence émotionnelle dans l’enseignement. L’article fait rapport des résultats d’une étude ayant porté sur l’intelligence émotionnelle, selon cinq dimensions, de 4 098 enseignants dans le Sultanat d’Oman en employant l’échelle de Schutte sur l’intelligence émotionnelle. L’étude a également mesuré le rapport entre l’intelligence émotionnelle des enseignants et un certain nombre de variables démographiques liées aux enseignants et aux écoles. Les résultats indiquent que l’intelligence émotionnelle des enseignants étaient élevée pour toutes les dimensions. Des variations dans l’intelligence émotionnelle des enseignants se sont révélées selon les variables liées aux enseignants et aux écoles. Mots clés : satisfaction professionnelle; Sultanat d’Oman; intelligence émotionnelle chez les enseignants Saleh Al-Busaidi1, Said Aldhafri12, Marwa Alrajhi1, Hussain Alkharusi1, Bader Alkharusi3, Abdullah Ambusaidi1, Khoula Alhosni3